IN VITRO EVALUATION OF SUGARCANE TOPS BASED COMPLETE FEED - R. Prabakaran; M. Ramachandran; K. Ayyappan; V. Sasikala (Indian Journal of Veterinary and Animal Sciences Research, 2026)
The present research work was carried out to evaluate the effect of inclusion of different levels of sugarcane tops and different levels of crude protein in the complete feed on in vitro parameters. Three complete feeds were prepared with three different crude protein levels of 8%, 10% and 12% utilizing sorghum stover as a roughage source. Twelve sugarcane tops based complete feeds were prepared by replacing sorghum stover with sugarcane tops at four different levels of 25%, 50%, 75% and 100%, with three different crude protein levels (8%, 10% and 12%) in each level of inclusion. Total digestible nutrients of 50% and roughage:concentrate ratio of 65:35 have been maintained in all the fifteen complete feeds (CFE 1 to CFE 15). There was a significant difference (P<0.01) in organic matter, crude fibre, total ash, acid insoluble ash, neutral detergent fibre, acid detergent fibre, acid detergent lignin, cellulose and hemicellulose contents (%) among complete feeds. In vitro gas production (ml/48 hours/200mg) and in vitro dry matter degradability (%) of complete feeds did not differ significantly (P>0.05) among complete feeds. In vitro organic matter degradability (%) was significantly higher (P<0.05) at 75% and 100% replacement of sorghum stover with sugarcane tops. Based on the results of the experiment, it can be concluded that different levels of crude protein in the compete diets did not have any effect on the in vitro parameters except in vitro organic matter degradability, which was significantly higher (P<0.05) at 75% (CFE 10, 11 and 12) and 100% (CFE 13, 14 and 15) replacement of sorghum stover with sugarcane tops.